2020
DOI: 10.1080/23311916.2020.1807082
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization for the green vehicle routing problem: A systematic literature review and future directions

Abstract: This article aims to present research conducted on the literature regarding multi-objective optimization for routing problems with environmental considerations, referred to here as Multi-objective Optimization for the Green Vehicle Routing Problem (MOOGVRP). A Brazilian database, CAPES (Coordination for the Improvement of Higher Education Personnel), was used to collect articles of general application, case studies and reviews in English starting from, since 2012. The terms "green vehicle routing problem" (GVR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Ferreira et al [18] reviewed 76 papers concerning the multi-objective version of GVRP, from 2012 to 2018. It primarily concentrated on the bibliometric analysis of ICV-based papers, including PRP, GVRP, and reverse logistics, while AFV-based papers were not considered.…”
Section: Previous Surveys On Gvrpmentioning
confidence: 99%
“…Ferreira et al [18] reviewed 76 papers concerning the multi-objective version of GVRP, from 2012 to 2018. It primarily concentrated on the bibliometric analysis of ICV-based papers, including PRP, GVRP, and reverse logistics, while AFV-based papers were not considered.…”
Section: Previous Surveys On Gvrpmentioning
confidence: 99%
“…Routing optimization in the context of EnFVs involves the determination of efficient and optimal routes for message transmission, considering various objectives and constraints [17,18]. The objectives in multi-objective message routing optimization typically include minimizing message delivery time, maximizing network throughput, reducing energy consumption, and ensuring reliable communication.…”
Section: Objectives and Constraints In Routing Optimizationmentioning
confidence: 99%
“…There is a critical need to develop routing algorithms that can effectively optimize message routing in these dynamic transportation systems and address the limitations of traditional routing algorithms [18]. Multi-objective optimization is highly important in the context of EnFVs due to several key reasons [10,14,23]:…”
Section: Importance Of Multi-objective Optimization In Enfvsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that recent and comprehensive review on GVRSP from various perspectives can be found in Moghdani et al [38] and Ferreira et al [39].…”
Section: Optimization and Scheduling Groupmentioning
confidence: 99%